Digital art - Paul, Christiane (London : Thames & Hudson, 2003)
Digital technology has revolutionized the way we produce and experience art today. Not only have traditional forms of art such as printing, painting, photography and sculpture been transformed by digital tecniques and media, but entirely new forms such as net art, software art, digital installation and virtual reality have emerged as recognized artistic practices, collected by major museums, institutions and private collectors the world over. Here Christiane Paul surveys the developments in digital art from its appearance in the 1980s up to the present day, and looks ahead to what the future may hold. Drawing a distinction between work that uses digital technology as a tool to produce traditional forms and work that uses it as a medium to create new types of art, she discusses the key artists and works. The book eexplores themes addressed and raised by the art, such as viewer interaction, artificial life and intelligencen political and social activism, networks and telepresence, as well as issues such as the collection, presentation and preservation of digital art.
0100101110101101.org ; Achituv, Romy ; Allen, Rebecca ; Apóstol, Alexander ; Arcangel, Cory ; ART + COM ; Asymptote ; Bauer, Will ; Bear, Liza ; Blair, David ; Bohn, Christian A. ; Bookchin, Natalie ; Bradford Paley, W. ; Brenneis, Lisa ; Buckhouse, James ; Burson, Nancy ; Campbell, Jim ; Campus, Peter ; Canny, John ; Canogar, Daniel ; Chafe, Chris ; Chapman, Adam ; Cohen, Charles ; Cohen, Janet ; Condon, Brody ; Courchesne, Luc ; Crowe, Nick ; Csuri, Charles ; D'Agostino, Peter ; Davies, Charlotte ; Davis, Douglas ; Donath, Judith ; Dove, Toni ; Duchamp, Marcel ; Eager, Hal ; etoy ; Feinberg, Jonathan ; Feingold, Kenneth ; Feng Mengbo ; Fleischmann, Monika ; Frank, Keith ; Fry, Benjamin ; Fudge, Carl ; Fujihata Masaki ; Galloway, Alex ; Galloway, Kit ; Gasperini, Jim ; Gilbert, Jesse ; Goldberg, Ken ; Gonzales-Day, Ken ; Griesbach, Scott ; Hachiya Kazuhiko ; Harwood, Graham ; Hegedüs, Agnes ; Hendricks, Jochem ; Hershman, Lynn ; Hoberman, Perry ; Houshmand, Zara ; Huber, Dieter ; Huyghe, Pierre ; Ippolito, Jon ; Iwai, Toshio ; James, Mark ; Jenik, Adriene ; Jeremijenko, Natalie ; Jevbratt, Lisa ; Jodi ; Kaap, Gerald Van Der ; Kac, Eduardo ; Kalpakjian, Craig ; KIDing ; Klima, John ; LaPorta, Tina ; Latham, William ; Lazzarini, Robert ; Leandre, Joan ; Legrady, George ; Levin, Golan ; Lialina, Olia ; Lozano-Hemmer, Rafael ; Maeda, John ; Mann, Steve ; Marton, Ana ; May, Gideon ; McCoy, Jennifer & Kevin ; Moholy-Nagy, Laszlo ; Moss, Brion ; Müller-Pohle, Andreas ; Muntadas, Antoni ; Naimark, Michael ; Napier, Mark ; Nechvatal, Joseph ; Neidich, Warren ; Nicolai, Carsten ; Nideffer, Robert ; Niemeyer, Greg ; On, Josh ; Paik, Nam June ; Palakunnathu Matthew, Annu ; Parreno, Philippe ; Paterson, Nancy ; Paulos, Eric ; Peljhan, Marko ; Piccinini, Patricia ; etc.
boek